Patient and Surrogate Postenrollment Perspectives on Research Using the Exception From Informed Consent: An Integrated Survey - Scicluna, Victoria M.; Biros, Michelle; Harney, Deneil K.; Jones, Elizabeth B.; Mitchell, Andrea R.; Pentz, Rebecca D.; Silbergleit, Robert; Speight, Candace D.; Wright, David W.; Dickert, Neal W. (Annals of emergency medicine, 2020)
It is important for researchers interested in trials using the exception from informed consent to understand the views and experiences of enrolled individuals. Previous studies have shown that patient and surrogate attitudes are generally positive. These studies were small and did not include pediatric patients, and interviews were often conducted long after trial enrollment. This study sought to explore attitudes toward exception from informed consent in a larger sample and more contemporaneous setting. A 10-item paper-and-pencil survey was integrated into the Established Status Epilepticus Treatment Trial, a randomized trial of 3 treatments for benzodiazepine-refractory status epilepticus in pediatric and adult patients. Primary domains included attitudes toward trial enrollment, exception from informed consent, and community consultation. Simple descriptive statistics, χ2, and Fisher’s exact tests were conducted. Of 317 patients and surrogates, 90% agreed with or were neutral about the statement “I am glad that I/my family member was included in the Established Status Epilepticus Treatment Trial research study,” whereas 10% disagreed. Twenty-seven percent disagreed with enrollment in the study without prospective consent. Black participants were more likely than white, other race, and unknown-race participants to disagree with enrollment without prospective consent (36% versus 23%, 14%, and 14%, respectively). Participants indicated that patients (81%), their families (65%), and those at risk for seizures (51%) were most important to include in community consultation. This study aimed to explore attitudes toward exception from informed consent enrollment among participants at all sites in a large, multicenter exception from informed consent trial. General acceptance of trial enrollment was high; acceptance of exception from informed consent specifically was somewhat lower, especially among black participants. Our findings provide further support for targeted community consultation focusing on individuals with connections to the disease under study. Future research should focus on communication in the postenrollment period, especially with individuals who may have concerns about exception from informed consent.